The individual: An unresolved issue for sociology - Santiago, Jose; Martuccelli, Danilo (Convergencia Revista de Ciencias Sociales; Vol. 29 (2022), 2022)
This article aims to vindicate the importance of the individual for sociology. Its main objective is to discuss and problematise the way in which various sociological perspectives (classical sociology, the action-structure debate, microsociology, methodological individualism, dispositionalist sociologies, the individualization thesis and the new institutional individualism, the sociology of social trials) have theorised the individual and the place it should occupy in sociology. We offer a critical review of each of these sociological approaches, showing some of their weaknesses and their potential to analyse current societies and the type of individual they produce. In this way, this article defends the project of a sociology of the individual that makes the individual a primary heuristic tool to understand our societies at a time when there is increasing demand for forms of social representation rooted in individual experiences.